Pembuatan Jadwal Retensi Arsip (JRA) di Kantor Wali Nagari Kajai Kabupaten Pasaman Barat - Oktarino Arizola; Elva Rahmah (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
This paper discusses the making of Records Retention Schedule (RRS) in the Office of the Nagari Kajai West Pasaman. The of writing of this paper to describe the process of making RRS in the Office of the Nagari Kajai West Pasaman. RRS making process in the Office of the Nagari Kajai, West Pasaman started to browse the archive of information that will be made retention schedule, selecting, and classifying records, as well as the collection of data. Based on the data analysis it can be concluded, first, that there are records in the Office of the Nagari Kajai can be classified into three categories, namely class script vital, important slip sand slip shandy. Second, in the manufacture of Records Retention Schedule take steams of each head of affairs and secretary. Third, conduct a survey to look at the purpose and functions of the organization, the vision and mission of the organization as well as archived data stored. Fourth, the archive data collection form survey or inventory records.Keywords: Records Retension Schedule;archive